Alternative splicing for tuneable expression of protein subunits at desired ratios - Christel Aebischer-Gumy; Pierre Moretti; Timothee Brunstein Laplace; Jana Frank; Ysaline Grand; Farid Mosbaoui; Emilie Hily; Anna Galea; Megane Peltret; Carole Estoppey; Daniel Ayoub; Roberto Giovannini; et al. (mAbs)
The controlled expression of two or more proteins at a defined and stable ratio remains a substantial challenge, particularly in the bi- and multispecific antibody field. Achieving an optimal ratio of protein subunits can facilitate the assembly of multimeric proteins with high efficiency and minimize the production of by-products. In this study, we propose a solution based on alternative splicing, enabling the expression of a tunable and predefined ratio of two distinct polypeptide chains from the same pre-mRNA under the control of a single promoter. The pre-mRNA used in this study contains two open reading frames situated on separate exons. The first exon is flanked by two copies of the chicken troponin intron 4 (cTNT-I4) and is susceptible to excision from the pre-mRNA by means of alternative splicing. This specific design enables the modulation of the splice ratio by adjusting the strength of the splice acceptor. To illustrate this approach, we developed constructs expressing varying ratios of GFP and dsRED and extended their application to multimeric proteins such as monoclonal antibodies, achieving industrially relevant expression levels (>1 g/L) in a 14-day fed-batch process. The stability of the splice ratio was confirmed by droplet digital PCR in a stable pool cultivated over a 28-day period, while product quality was assessed via intact mass analysis, demonstrating absence of product-related impurities resulting from undesired splice events. Furthermore, we showcased the versatility of the construct by expressing two subunits of a bispecific antibody of the BEAT® type, which contains three distinct subunits in total.